The effect of water potential and deterioration on some indices of germination and biochemical of linseed (Linum usitatissimum Var. Norman) seed at different temperatures - Ali Hoseinipoor; Alireza Yadavi; Hamidreza Balouchi; َAli Moradi (علوم و فناوری بذر ایران)
Germination is one of the most sensitive stages of plant life, which is affected by various environmental factors such as temperature and humidity. Because seed standard germination test alone cannot accurately describe seedling emergence in field conditions, seed strain tests such as accelerated aging test (seed deterioration) are used. In this research, germination and biochemical indices of linseed (‌Linum usitatissimum Var. Norman) in moisture potential of 0, -0.2, -0.4, -0.6, -0.8, -1.2 and -1.2 MPa under accelerated aging conditions at temperatures 10, 15, 20, 25, 30 and 35°c were evaluated. The results showed that the percentage and rate of germination and seedling vigor index in accelerated aging and non-accelerated aging respectively were increased by increasing temperature up to 20 and 25 ° C, , then decreasing to 35 ° C. And with decreasing potential water, in terms of accelerated aging, showed its lowest level at any temperature. The amount of soluble protein, catalase activity and proline content of seeds increased with decreasing water potential and accelerated aging effects at each temperature. Also, with increasing temperature, protein content and catalase enzyme activity of Linum usitatissimum seed are increased; proline content of the seed decreased.The results of this study showed that Linum usitatissimumis resistant to high and low temperatures in the early stages of germination under favorable temperature conditions of plants resistant to dehydration and under stress-free conditions.